Genomic Insights into Genetic Diploidization in the Homosporous Fern Adiantum nelumboides. (10th August 2022) - Zhong, Yan; Liu, Yongbo; Wu, Wei; Chen, Jingfang; Sun, Chenyu; Liu, Hongmei; Shu, Jiangping; Ebihara, Atsushi; Yan, Yuehong; Zhou, Renchao; Schneider, Harald
Abstract: Whole-genome duplication has been recognized as a major process in speciation of land plants, especially in ferns. Whereas genome downsizing contributes greatly to the post-genome shock responses of polyploid flowering plants, diploidization of polyploid ferns diverges by maintaining most of the duplicated DNA and is thus expected to be dominated by genic processes. As a consequence, fern genomes provide excellent opportunities to study ecological speciation enforced by expansion of protein families via polyploidy. To test the key predictions of this hypothesis, we reported the de novo genome sequence of Adiantum nelumboides, a tetraploid homosporous fern. The obtained draft genome had a size of 6.27 Gb assembled into 11, 767 scaffolds with the contig N50 of 1.37 Mb. Repetitive DNA sequences contributed with about 81.7%, a remarkably high proportion of the genome. With 69, 568, the number of predicted protein-coding genes exceeded those reported in most other land plant genomes. Intragenomic synteny analyses recovered 443 blocks with the average block size of 1.29 Mb and the average gene content of 16 genes. The results are consistent with the hypothesis of high ancestral chromosome number, lack of substantial genome downsizing, and dominance of genic diploidization. As expected in the calciphilous plants, a notable number of detected genes were involved in calcium uptake and transport. In summary, the genome sequence of a tetraploid homosporous fern not only provides access to a genomic resource of a derived fern, but also supports the hypothesis of maintenance of high chromosome numbers and duplicated DNA in young polyploid ferns.